Strategi Layanan pada Dinas Perpustakaan dan Kearsipan (DISPUSIPDA) Jawa Barat Di Masa Pandemi COVID-19 - Neneng Komariah; Khariema Ratih (Institut Agama Islam Negeri (IAIN) Curup, 2022)
The presence of COVID-19 causes libraries must create new service strategies to continue to provide services to users. The purpose of the study was to know how the West Java Dispusipda Library service strategy during the COVID-19 pandemic. The research focus on how the library manage direct service strategy, how to manage Candil digital library services, and Makan Jengkol book delivery service. This study uses a qualitative method with data collection techniques interview, observation, documentation, and literature study. Interviews were conducted on two informants. Data analysis consists of data reduction, data display, and data verification. The results showed that direct services at the West Java Dispusipda Library were carried out by implementing health protocols and special rules, as well as open and closed services. Candil digital library services is application-based digital libraries that provide almost 13000 books. It can be downloaded on Playstore or Appstore for free. The Makan Jengkol Service is a book borrowing and returning service which provides 150 book titles. It can be used by utilizing Grabexpress. Conclusion The West Java Dispusipda Library is able to continue to provide information access services to the public during the COVID-19 pandemic, both direct services and online services